Effect of selected pesticides on conidial germination and mycelial growth of Dactylaria higginsii, a potential bioherbicide for purple nutsedge (Cyperus rotundus) - Yandoc, Camilla B.; Rosskopf, E. N.; Pitelli, R. L.C.M.; Charudattan, R. (Cambridge University Press (CUP), 2006)
The suitability of a bioherbicide as a component of an integrated weed management program not only relies on its field efficacy, but also on its compatibility with other pest control measures that may be employed during the cropping season. The effects of selected pesticides applied according to label rates on Dactylaria higginsii, a biological control agent for purple nutsedge, were determined using mycelial growth on pesticide-amended potato dextrose agar (PDA) and conidial germination as indicators of pesticide sensitivity. Among the pesticides tested, the herbicides oxyfluorfen and sethoxydim and the fungicides fosetyl-Al and thiophanate methyl inhibited D. higginsii mycelial growth and reduced or completely inhibited conidial germination; the herbicide diuron, the fungicides metalaxyl and copper hydroxide, and the insecticide cyromazine reduced mycelial growth but did not reduce conidial germination. The miticide dicofol reduced mycelial growth and completely inhibited conidial germination while the herbicide imazapyr had no adverse effect on either the mycelial growth or conidial germination of D. higginsii.
Keywords: Bioherbicide; Biological control; Conidial germination; Pesticide sensitivity